Integration of Ocean Literacy into Physics Learning - Santoso, Purwoko Haryadi (Program Studi Pendidikan Fisika UHAMKA, 2019)
Indonesia will be projected to be maritime axis in the world. Indonesian potential as a maritime country inspires Nawacita vision established by Joko Widodo in his cabinet. This ambitions must be supported by coastal communities. The province of West Sulawesi has a long coastal territory than other provinces in Indonesia. It should be exploited to promote the realization of Nawacita for the better Indonesia in the future. In education sector, 2013 curriculum introduces that teachers must implement scientific approach to their learning. Physics is one of the subjects that is still considered difficult by students. It will be more complex when it is taught by scientific approach. In other hand, physics is one of the most important subjects in preparing high school students for their job in science and technology. Contextual learning could be a solution in delivering physics to students. Without forgetting the 2013 curriculum, physics learning in the context of ocean literacy owned by West Sulawesi can lead students to gain meaningful experience. Based on these considerations, this article will discuss how to integrate ocean literacy into physics learning.